Relation of Serum Hepcidin Levels and Restless Legs Syndrome in Patients Undergoing Peritoneal Dialysis - Guo, Yanhong; Sang, Yuan; Pu, Tian; Li, Xiaodan; Wang, Yulin; Yu, Lu; Liang, Yan; Wang, Liuwei; Liu, Peipei; Tang, Lin (Frontiers in Medicine, 2021)
Introduction: Restless legs syndrome(RLS) is a common and severe complication in peritoneal dialysis (PD) patients, which seriously affects the quality of life and prognosis of PD patients. But unfortunately, there are still no effective prevention and treatment measures 1. Serum hepcidin was demonstrated to be related with primary RLS, whereas there are no studies on the relationship between serum hepcidin and RLS in PD patients. We aimed to evaluate the role and function of serum hepcidin in PD patients with RLS. Methods: A total of 51 PD patients with RLS and 102 age-and gender- matched PD patients without RLS were included. We collected the clinical data including serum hepcidin of those PD patients. The severity of RLS was scored according to the International restless leg Syndrome Research Group rating scale (IRLS). The clinical characteristics of the two groups were compared; the risk factors of RLS were evaluated by Logistic regression analysis; the diagnostic value of serum hepcidin in PD patients with RLS was evaluated by receiver operating characteristic (ROC) curve; and the influencing factors of IRLS were analyzed by multivariate linear regression analysis. Results: Among the two groups, duration of PD, serum hepcidin, and calcium were found to be significantly higher in PD patients with RLS than those in PD patients without RLS (p<0.001, p<0.001, and p = 0.002, respectively). The level of hemoglobin and albumin were significantly lower in PD patients with RLS (p=0.002, and p = 0.042, respectively). Duration of PD (OR 1.033, 95% CI: 1.017, 1.050, P<0.001), calcium level (OR 8.176, 95% CI: 2.062, 32.424, P=0.003), and serum hepcidin level (OR 1.026, 95% CI: 1.013, 1.039, P<0.001) are risk factors associated with RLS in PD patients. Hemoglobulin level (OR 0.970, 95% CI: 0.951, 0.989, P=0.002) and albumin level (OR 0.860, 95% CI: 0.798, 0.927, P<0.001) are protecting factors associated with RLS in PD patients. A multivariate linear regression analysis revealed that they also are independently associated with the severity of RLS. Conclusion: A significant relation was detected between serum hepcidin level and RLS in PD patients.